OJEK SAYUR DI DESA LUBUK BEDORONG 2003 – 2024 - Susanti, Susanti; Karmela, Siti Heidi; Azmi, Ulul (Universitas Batanghari Jambi, 2025)
This research is a historical research with an economic theme. The main problem in this research is the economic life of Vegetable Ojek operators in Lubuk Bedorong Village from 2003 to 2024. For this reason, a problem formulation will be made with several questions that will be discussed more clearly in the following chapters, namely; How has the development of vegetable ojek in Lubuk Bedorong Village and Why vegetable ojek still survives in Lubuk Bedorong Village until now. The method used in this research is a historical research method consisting of several stages, namely heuristics, criticism, interpretation, and historiography. The primary source used in this research is an interview with vegetable ojek operators, village elders, and the community in Lubuk Bedorong Village. While secondary sources used are books, theses, journals and internet sources. The results of the study provide an explanation where vegetable ojek operators who trade in Lubuk Bedorong Village have a prosperous life where they are able to send their children to school and meet their family's needs and vegetable ojek has a much-needed impact on the community in Lubuk Bedorong Village who still operates trading in the Village.